The most good you can do how effective altruism is changing ideas about living ethically - Singer, Peter 1946- (Castle lectures in ethics, politics, and economics, 2015)
The Most Good You Can Do develops the challenges Singer has made to those who donate to the arts, and to charities focused on helping our fellow citizens, rather than those for whom we can do the most good. Effective altruists are extending our knowledge of the possibilities of living less selfishly, and of allowing reason, rather than emotion, to determine how we live. The Most Good You Can Do offers new hope for our ability to tackle the world's most pressing problems.